Structural Design and Analysis of an Omni-Directional Mosbile Stair Climbing Wheelchair - Zhou Qiuyu; Xing Xiaodong (Jixie chuandong)
An omni-directional mobile stair climbing wheelchair is designed to help the persons with lower limb disabilities climb the stairs.The function of climbing stair of the wheelchair is realized by using mechanical support legs and wheels bearing the wheelchair alternately.Four Mecanum wheels are taken as the wheelchair wheels and driven by four electrical motors.The capability of obstacle crossing with the limited width of stairs and the kinematical and dynamics math model are analyzed.The anteroposterior and lateral stability of the wheelchair are analyzed with combining energy method and stability reserve analysis method.The characteristics of omni-directional movement of the wheelchair are also studied.The result shows that the wheelchair can climb most stairs safely and wouldn’t turn over.The omni- directional movement can be achieved by controlling the speed of four wheels.The structural design of the wheelchair is reasonable.And the combination of the stair- climbing function and the omni- directional mobile function is realized successfully.